"Today I Apologise" A Postcolonial Perspective on the Apologies Offered by the Dutch State to Their Former Caribbean Colonies - Groot,Jet (2024)
In 2022 and 2023, the prime minister and king of the Netherlands offered their official apologies on behalf of the Dutch state to the former Caribbean colonies for the injustices of slavery and colonialism. These apologies aimed to address both historical transgressions and the contemporary legacies of the injustices. This thesis studies how the apologies by the prime minister and king framed the power relations between the Dutch state and its former colonies. Political apologies for historical injustices and postcolonial narratives alike have been criticised for maintaining racialised discourses and unequal relations of power. Using a postcolonial perspective and discourse-historical approach, this thesis analyses how language has been used to reflect these expressions of power that protect the image and interests of the Dutch state. The study finds that the apologies refrained from explicit problematic discourses and positively promoted reconciliation by advocating for ongoing dialogue. Instead, the analysis revealed a nuanced representation of power. The prime minister and king distanced themselves from past actions and avoided responsibility for the contemporary legacies of colonialism. This resulted in a limited offer of commitments towards structural reparations. Furthermore, the apologies largely excluded the voices of the former colonies. These discursive strategies have maintained a one-sided narrative that favours the Dutch state as the former colonisers. Thus, while the former colonies have perceived the apologies as meaningful, the acts demonstrated problematic discourses similar to other political apologies for colonialism.
Keywords: political apologies; colonialism; slavery; the Netherlands; Dutch Caribbean; postcolonialism; discourse analysis; colonial reparations; contemporary legacies of colonialism